Pharmacological characterization of the small molecule 03A10 as an inhibitor of α-synuclein aggregation for Parkinson’s disease treatment - Wang Qing; Yao Sheng; Yang Ze-xian; Zhou Chen; Zhang Yu; Zhang Ye; Zhang Lei; Li Jin-tian; Xu Zhi-jian; Zhu Wei-liang; Zhang Nai-xia; Ye Yang; et al. (Acta Pharmacologica Sinica, 2023)
Aggregation of α-synuclein, a component of Lewy bodies (LBs) or Lewy neurites in Parkinson’s disease (PD), is strongly linked with disease development, making it an attractive therapeutic target. Inhibiting aggregation can slow or prevent the neurodegenerative process. However, the bottleneck towards achieving this goal is the lack of such inhibitors. In the current study, we established a high-throughput screening platform to identify candidate compounds for preventing the aggregation of α-synuclein among the natural products in our in-house compound library. We found that a small molecule, 03A10, i.e., (+)-desdimethylpinoresinol, which is present in the fruits of Vernicia fordii (Euphorbiaceae), modulated aggregated α-synuclein, but not monomeric α-synuclein, to prevent further elongation of α-synuclein fibrils. In α-synuclein-overexpressing cell lines, 03A10 (10 μM) efficiently prevented α- synuclein aggregation and markedly ameliorated the cellular toxicity of α-synuclein fibril seeds. In the MPTP/probenecid (MPTP/p) mouse model, oral administration of 03A10 (0.3 mg· kg−1 ·d−1, 1 mg ·kg−1 ·d−1, for 35 days) significantly alleviated behavioral deficits, tyrosine hydroxylase (TH) neuron degeneration and p-α-synuclein aggregation in the substantia nigra (SN). As the Braak hypothesis postulates that the prevailing site of early PD pathology is the gastrointestinal tract, we inoculated α-synuclein preformed fibrils (PFFs) into the mouse colon. We demonstrated that α-synuclein PFF inoculation promoted α-synuclein pathology and neuroinflammation in the gut and brain; oral administration of 03A10 (5 mg· kg−1 ·d−1, for 4 months) significantly attenuated olfactory deficits, α-synuclein accumulation and neuroinflammation in the olfactory bulb and SN. We conclude that 03A10 might be a promising drug candidate for the treatment of PD.